ANALISIS PENGARUH KARAKTERISTIK CORPORATE GOVERNANCE TERHADAP KETERJADIAN RESTATEMENT - Ridho Widi Kusumo; Wahyu Meiranto (Diponegoro Journal of Accounting, 2014)
The purpose of this study was to examine the effect of corporate governance characteristics on the financial restatement. Indicators used to measure corporate governance mechanisms in this study is the size of board, proportion of independent board, size of audit committee, managerial ownership,and institutional. While financial restatement as the dependent variable was measured using dummy variabel which used number 1 for restatement companies and number 0 for non-restatement companies. In addition, this study also added two control variables are firm size firm size and leverage.This study uses secondary data with entire population companies listed in the Indonesia Stock Exchange (BEI) in 2008-2012. The method used to determine the sample using purposive sampling. Sample contains from 24 restate companies and 24 non-restate companies. The criteria of restatement companies allowed from GAO’s definition of restatement and exclude restatement that was happened due to application of new PSAK, accounting method changes, merge and acquisition that accordance with PSAK, and stock splits or reverse stock. The analytical method used is logistic regression.The results of hypothesis testing showed that the proportion of independent board and institutional ownership negatively affects the financial restatement.. While size of board, size of audit committee and managerial ownership did not significantly affect restatement. Overall it can be concluded from these results that the corporate governance characteristics affect with occurance of restatement.